2019
DOI: 10.1123/jsr.2017-0360
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Shoulder Injury in Elite Wheelchair Athletes Differ Between Sports: A Critically Appraised Topic

Abstract: Clinical Scenario: Until recently, injury epidemiology data on elite Paralympic athletes were limited. Current data suggest high rates of shoulder injury in wheelchair athletes. Differences in shoulder injury rates between sports have not been reported in this population. Clinical Question: Is the incidence of shoulder injury in elite wheelchair athletes different between sports? Summary of Key Findings: Shoulder injury rates are high in elite wheelchair athletes, particularly in sports such as field events an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…The scientific literature has demonstrated that the identification of factors that generate injuries and/or trauma, their prevalence, their type, and their nature are important issues for sports science [6,[13][14][15][16][17][18]. Only proper recognition of this problem is the basis for optimal training, without compromising the health of the athlete.…”
Section: Discussionmentioning
confidence: 99%
“…The scientific literature has demonstrated that the identification of factors that generate injuries and/or trauma, their prevalence, their type, and their nature are important issues for sports science [6,[13][14][15][16][17][18]. Only proper recognition of this problem is the basis for optimal training, without compromising the health of the athlete.…”
Section: Discussionmentioning
confidence: 99%
“…The research concerned with wheelchair fencing conducted to this date has focused on the issues relating to injuries that wheelchair fencers are subjected to [2][3][4][5]. A significant proportion of the research involves physiological and conditioning determinants of achievement potential in this sport [6] and various aspects of kinematics of movement patterns performed by disabled fencers [7].…”
Section: Introductionmentioning
confidence: 99%
“…In elite wheelchair athletes, upper limb injuries are frequent, with shoulder injuries being the most common (Fairbairn et al, 2019;Tuakli-Wosornu et al, 2018). The cause of shoulder problems in wheelchair athletes is probably multifactorial and is difficult to identify (Heyward, 2017).…”
Section: Introductionmentioning
confidence: 99%